The Potency of Catechin from Gambir (Uncaria gambir Roxb.) as a Natural Inhibitor of MurA (1UAE) Enzyme: In vitro and In silico studies - Riyana, Bella; Huspa, Desi H. P.; Satari, Mieke H.; Kurnia, Dikdik (Letters in Drug Design & Discovery, 2020)
Background: Currently, infectious diseases caused by pathogenic and resistant bacteria are more challenging for anti-bacterial drug discovery. The discovery of new anti-bacterial agents developed in many mechanisms includes disruption of the bacterial cell wall formations. The MurA is a key enzyme contributing to the first step of bacterial peptidoglycan biosynthesis and is, therefore, proposed as an effective bactericidal target. Objective: The purpose of this research is to identify anti-bacterial compounds from U. gambir Roxb and to predict the potential inhibitory activities against murA enzyme by in silico study. Materials and Methods: Investigation and discovery of new inhibitors of MurA enzyme were conducted on the medicinal plant of Gambir (Uncaria gambir Roxb) and those that reportedly contained anti-bacterial agents. The anti-bacterial compounds were isolated by combinations of chromatography methods guided by anti-bacterial activity against bacteria of E. faecalis, S. mutans, and S. sanguinis. The structures of active compounds were characterized by spectroscopic methods, and the anti-bacterial activity was evaluated by the microdilution method (in vitro) combined with molecular docking of the MurA enzyme (in silico). Results: The anti-bacterial flavonoids of catechin were isolated from U. gambir Roxb with MIC values of 6250 and 12500 ppm, respectively, against S. sanguinis and E. faecalis. The in silico study showed that catechin has a binding affinity of -8.5 Kcal/mol to MurA which is higher than fosfomycin as a positive control. Conclusions: The catechin is predicted to have potential as a new natural inhibitor of the MurA enzyme to inhibit bacterial cell wall biosynthesis.
Keywords: MurA enzyme